PENANAMAN NILAI AGAMA DAN MORAL MELALUI PEMBIASAAN BERDOA TERHADAP PEMBENTUKAN AKHLAK SISWA DI RA HASAN MUNADI GUNUNG GANGSIR BEJI PASURUAN - Saleh, Nanang Rokhman; Syaikhon, Muhammad (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
The impact of globalization and the rapidly development of the times marked by digitalization has made moral education in early childhood decrease drastically. Many children still commit deviant acts, acts of violence, behave badly and commit acts that are prohibited in religion. This can happen because of the lack of religious and moral cultivation from an early age. Therefore, the most important thing to do is an effort to form a moral human being by instilling religious and moral values through the habituation of prayer. Raudhatul Athfal (RA) Muslimat Hasan Munadi is one of the educational institutions under the auspices of the Ministry of Religion that implements the cultivation of religious and moral values through habituation to prayer. This study aims to analyze the cultivation of religious and moral values through habituation of prayer towards the formation of student morals in RA Hasan Munadi Gunung Gangsir Beji Pasuruan. The data sources in this study consist of primary sources in the form of school data, while secondary data are the results of observation, interviews, and documentation. Data collection techniques through observation, interview, and documentation methods. The data analysis technique uses the Miles and Huberman analysis method so that it can be seen the implementation of the cultivation of religious and moral values through the habituation of prayer towards the formation of student morals at RA Hasan Munadi. The results showed that the cultivation of religious and moral values through the habituation of prayer towards the formation of student morals at RA Hasan Munadi was optimally implemented in accordance with expectations and developmental achievements